2021
DOI: 10.1111/ejn.15448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture and body weight loading on spinal posterior root reflex responses

Abstract: The posterior root muscle response (PRM) is a monosynaptic reflex that is evoked by single pulse transcutaneous spinal cord stimulation (tSCS). The main aim of this work was to analyse how body weight loading influences PRM reflex threshold measured from several lower limb muscles in healthy participants. PRM reflex responses were evoked with 1-ms rectangular monophasic pulses applied at an interval of 6 s via a self-adhesive electrode (9 Â 5 cm) at the T11-T12 vertebral level. Surface electromyographic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, the main limitation to determining the real effectiveness of tsDCS was the variability in the obtained results, which are in line with those seen by other authors. Several reasons could explain this variability, namely the orientation of spinal circuits relative to the direction of current,48,49 the distance between electrodes,48,49 polarity,48,49 body tissue composition,50 and position,51 similar to other transcutaneous spinal stimulation techniques 52. Furthermore, the included studies employed 3 different positions during stimulation, hindering their comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main limitation to determining the real effectiveness of tsDCS was the variability in the obtained results, which are in line with those seen by other authors. Several reasons could explain this variability, namely the orientation of spinal circuits relative to the direction of current,48,49 the distance between electrodes,48,49 polarity,48,49 body tissue composition,50 and position,51 similar to other transcutaneous spinal stimulation techniques 52. Furthermore, the included studies employed 3 different positions during stimulation, hindering their comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons could explain this variability, namely the orientation of spinal circuits relative to the direction of current, 48,49 the distance between electrodes, 48,49 polarity, 48,49 body tissue composition, 50 and position, 51 similar to other transcutaneous spinal stimulation techniques. 52 Furthermore, the included studies employed 3 different positions during stimulation, hindering their comparison. Murray et al 51 found that cathodal tsDCS decreased intracortical facilitation when the patient was seated and increased tibialis anterior MEP when they were lying supine.…”
Section: Effectiveness Of Tsdcs Over Clinical and Neurophysiological ...mentioning
confidence: 99%
“…This implied increase in sEMR threshold intensity in participants with a SCI could be caused by differences in adipose tissue under the stimulation electrodes (Kuhn et al, 2009 ; Ladenbauer et al, 2010 ), although BMI was similar between groups. It could also reflect differences in body position as changes in spinal curvature or weight bearing through the lower limbs has been shown to influence sEMR stimulation intensity (Binder et al, 2021 ; Megía‐García et al, 2021 ; Militskova et al, 2020 ). In the present study, non‐SCI participants were suspended upright in a harness and participants with a SCI were titled to 55°.…”
Section: Discussionmentioning
confidence: 99%
“…As a therapeutic modality, TSS can produce short-term changes in spinal excitability that are believed to promote the reorganization of neural pathways (de Freitas et al 2021 ). Based on this assumption, TSS has been used in attempts to enable movements (Inanici et al 2021 ), reduce spasticity (Hofstoetter et al 2021 ), and improve autonomic functions (Samejima et al 2022 ) after spinal cord injury in humans, whether used alone (Megía-García et al 2021 ; Meyer et al 2020 ) or in combination with other rehabilitation strategies (Al’joboori et al 2020 ; Gad et al 2017 ; Hofstoetter et al 2021 ; Inanici et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%